Governance perspective: foreign investment in decentralization in Indonesia - Farhan, Eva Kurnia; Setiyono, Budi; Yuwono, Teguh; Dewi, Reni Shinta (Frontiers in Political Science, 2025)
Background and objectivesThis study explores the local governance dimension of South Sumatra, Indonesia, in the implementation of foreign investment (FI) and explains that local governments have the authority to regulate policies or only become facilitators in the provision of public goods and services. This study argues that local governments are still weak in managing foreign investment because they do not have full authority. This study addresses the problem of foreign investment in decentralization in Indonesia. Various political factors, including approving policies, granting political access, political lobbies, and agenda-setting, are important issues that need to be addressed.MethodsThe method used in this study employed a qualitative approach. The interview was conducted in several areas of South Sumatra province, such as Musi Rawas, Musi Rawas Utara, Empat Lawang, Lahat, and Musi Banyuasin. All analyses were performed using NVivo 12 plus.FindingsThe results of this study indicate that decentralization can increase the growth of economic and social development in a region because it promotes regional transparency, accountability, and responsiveness. However, a weakness of the local government is the absence of authority in the administrative capability of foreign investment. This is because the region is a facilitator and supervisor, following only central government regulations